Assessment of electric vehicle repurchase intention: A survey-based study on the Norwegian EV market - Saiful Hasan (Transportation Research Interdisciplinary Perspectives, 2021)
Electrification of vehicles is one of the most promising measures for decarbonising the transport system. Several countries worldwide have implemented policy incentives to promote mass electric vehicle (EV) adoption to mitigate the environmental and energy-related challenges caused by the increased demand for road transportation. As a result, the number of EVs on the road is growing in several countries. However, despite the growing demand, many consumers are still sceptical about EVs. The aim of this study is to evaluate consumers' EV repurchase intention by using an extended theory of planned behaviour (TPB). Studies on EV adoption have found TPB determinants of intention to be relevant. Additionally, this study argues that the effects of satisfaction should be considered in addition to the TPB elements to better understand repurchase intentions. Consequently, this study includes EV users' satisfaction with relevant aspects such as range-recharge, environmental attributes, cost, availability, symbolic attributes, and use-based policy measures. A structural equation model (SEM) was established to analyse a survey dataset consisting of 278 Norwegian EV owners. To assess satisfaction with EV use and the behavioural intention of EV repurchases, only the responses from actual EV users were studied. This is important because consumers with no prior experience with EVs tend to inaccurately portray their interest in a new product or service. The findings are of interest for both policymakers and EV manufacturers seeking to gain actionable insights into EV owners' needs and perceptions concerning EV attributes, thus developing and implementing better strategies to increase EV attractiveness and performance.